The meritocracy challenge - Mesquida Sampol, Joan (Razón y fe, 2022)
Meritocracy appears today as an ideological substratum that legitimizes the assignment of tasks and rewards, but its functioning is subject to accurate criticisms which, however, do not provide an alternative to this system. Catholic Social Teaching, however, does offer elements that allow us to place meritocracy in its proper place, subordinating it to certain values and, above all, to the idea of the common good. Far from denying the existence of different gifts and capacities in people, what is at stake is that these should be developed profitably within the framework of a true universal fraternity.
Keywords: meritocracy; Michael Sandel; Catholic Social Teaching; common good; universal destination of goods; fraternity